Impact of Storage on Alteration in Biochemical and Hematological Characteristics in Locally Donated Blood from Lampung Province: Assessing Potential Risks for Recipients - Yuniza, Filia; Nur Khoiriyah, Yustin; Danan Jaya, Bayu Putra (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
The utilization of stored blood for transfusion purposes is a common practice in Blood Transfusion Units worldwide. However, the storage period can induce various cellular alterations, potentially comprising the quality and efficacy of blood transfusions. This study aims to investigate changes in biochemical and hematological parameters in blood donors during the storage period. This study was a prospective study involving the observation of 10 blood bags collected from local community donors in Lampung Province. The blood samples were stored in CPDA-1 anticoagulant bags at a controlled temperature of 2-6 ° C for 35 days. At regular intervals of 7 days, comprehensive assessments were performed, encompassing complete blood parameters, electrolyte concentration (Na+, K+, Cl-), and blood pH levels. After 35 days of storage, statistically significant alterations were observed. Notably, there was a significant increase in hematocrit levels (p=0.000), mean corpuscular volume (MCV) (p=0.019), lymphocyte counts (p=0.000), and potassium concentrations (p=0.000). Conversely, mean corpuscular hemoglobin concentration (MCHC) (p=0.025), leukocyte counts (p=0.000), neutrophil counts (p=0.000), platelet counts (p=0.000), sodium levels (p=0.000), chloride levels (p=0.000), and pH values (p=0.000) were significantly declines. In conclusion, blood storage leads to notable alterations in biochemical and blood cell characteristics. Therefore, it is advisable to prioritize using fresh whole blood or blood stored for no more than seven days in transfusion practices to minimize the risk of post-transfusion reactions, especially in vulnerable recipients.  Keywords: Blood transfusion, biochemical changes, cellular changes, storage.